Factors affecting potato early dying in the San Luis Valley, Colorado - Davidson, Robert Day, author; Harrison, Monty D., committee member; Knutson, Kenneth W., committee member; McIntyre, Gary, committee member; Schwartz, Howard, committee member (Colorado State University. Libraries, 1994)
A three year comparison of Russet Burbank potatoes field grown in microplots containing combinations of Verticillium (V), Erwinia carotovora subsp. carotovora (Ecc) and E. c. subsp. atroseptica (Eca) inoculated into the seed and, in the case of Ecc, also applied in the irrigation water was conducted. Three levels of irrigation were used for all treatments. Verticillium appeared to have minimal impact. Plant stand, height and tuber numbers were not significantly different among treatments. Verticillium wilt or potato early dying (PED) progress was, in general, significantly greater than normal maturity in controls. Yield was significantly depressed in only one of three years. In the two warmest years, yields increased as irrigation increased. In the coolest year, the reverse was true with yields increasing as irrigation decreased. Greenhouse studies completed in 1989 showed that air temperature can play a major role in PED symptom development. Specialized chambers were held at three different air temperatures 15, 25 and 30°C with treatments similar to those used in the field studies. PED symptom progression was fastest under the highest temperature (30°C), but did not reach the same level of severity as found under lower temperatures. PED was greatest under the 25°C temperature, while almost non-existent at 15°C. Soil fumigation with BusanR resulted in reductions in Verticillium microsclerotial counts which were maintained for at least two further growing seasons. However, unfumigated soil also showed similar reductions in microsclerotial counts during the same time period. Ecc and Eca appeared to be the primary pathogens causing disease in the PED complex in the San Luis Valley, while V. dahliae appeared to have a secondary role. Synergistic V + Erwinia interactions were found. Progress of PED in V + Erwinia seed treatments was similar to or sometimes significantly greater than PED progress in plants exposed to either Erwinia or Verticillium alone. Yields were significantly lower than the control or either pathogen alone in three of the V + Erwinia seed treatments. Under pathogen combination treatments there was an obvious trend toward reduced yields and, as irrigation increased, toward increased PED severity, disease progress and yield loss. Erwinia carotovora treatments had significant reductions in stand in two of three years with Erwinia seed treatments, but not when Ecc was introduced through irrigation water. Overall, as irrigation and Erwinia inoculum density increased, stand loss increased. Tuber numbers and yields were, in general, depressed significantly under Erwinia seed treatments. In 1990 the high Ecc irrigation treatment under optimum moisture also significantly decreased yields. Erwinia infection of daughter tubers was greatest in the two cooler seasons. Overall, the higher the inoculum level used or the greater the water stress, the higher the infection rate.
Covers not scanned.
Keywords: Potatoes -- San Luis Valley (Colo. and N.M.)